2006
DOI: 10.1080/14786430600764880
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale global mixed ordering of B-site cations in Pb2M′M′′O6complex perovskite relaxors

Abstract: We have observed compositionally heterogeneous, uniformly distributed and closely interconnected nanoscale and sub-nanoscale domains in complex perovskite-structured relaxors. These domains are interpreted as originating from global mixed ordering, formed by numerous non-stoichiometric combinations of B-site cations across the entire bulk of the relaxor crystals and ceramics. The association between global mixed ordering and the origin of the forbidden reflections has been explained theoretically and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These findings are supported by the studies carried out by , suggesting that well ordered cation occupancies conflict with the notion of a 'space-charge' model and favour the 'random-site' model for the B-site long-range order. Long-range chemical clustering of B-site cations under certain conditions has been proposed to result in a specific superstructure in PST (Baba-Kishi et al, 2006). Positional displacements of the Pb ions on the A site are favoured by chemical ordering between Sc 3+ and Nb 5+ in PbSc 1/2 Nb 1/2 O 3 , as reported by Perrin et al (2001).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…These findings are supported by the studies carried out by , suggesting that well ordered cation occupancies conflict with the notion of a 'space-charge' model and favour the 'random-site' model for the B-site long-range order. Long-range chemical clustering of B-site cations under certain conditions has been proposed to result in a specific superstructure in PST (Baba-Kishi et al, 2006). Positional displacements of the Pb ions on the A site are favoured by chemical ordering between Sc 3+ and Nb 5+ in PbSc 1/2 Nb 1/2 O 3 , as reported by Perrin et al (2001).…”
Section: Introductionmentioning
confidence: 79%
“…Most relaxors, including PbMg 1/3 Nb 2/3 O 3 (PMN) and PST, have a tendency to undergo structural evolution and may be viewed as adaptable structures (Withers et al, 1994). The structural evolution could include chemical long-range order of various degrees associated with a superstructure on the (111) planes and development of an additional superstructure associated with long-range clustering of B-site cations on the (100) planes in PST (Baba-Kishi et al, 2006). In addition, A-site and B-site displacements occur as a combined result of lone-pair electrons on Pb 2+ and the necessity of meeting the valence requirements by the Pb 2+ ions, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition is now sharp with no frequency dispersion of the dielectric response, 45 Previous studies using transmission electron microscopy have shown that structural modulations and complex strain pattern exist in all PST samples examined, independent of their degree of order. [46][47][48][49] These structural modulations are related to the relaxor behavior in disordered PST as PNRs. Structural modulations in ferroelectric PST also break the cubic symmetry at T > T trans so that polar behavior is observed in the nominally cubic phase.…”
mentioning
confidence: 99%
“…Diffuse streaks along <110>* are observed in all major zone axes, indicating the presence of either planar defects or shortrange ordering along the directions. The ordered domains and the electrical properties of the ceramics suggest that the occurrence of diffuse streaks can be contributed by the large amount of short-range antiparallel polarization [5], polar nanoregions (PNRs) [6], various kind of nanoscale 1:1 ordering [4] and APBs. Relaxor behavior is given by the short-range polarization or polar nanoregions.…”
mentioning
confidence: 99%